Cephaeline promotes ferroptosis in breast cancer via p53/SLC7A11/GPX4 axis - Xiaohong Li; Jinghan Yu; Beibei Lin; Yudiao Gong (DARU Journal of Pharmaceutical Sciences, 2026)
Background Cephaeline (CPL), a bioactive compound derived from the medicinal plant Ipecacuanha, has demonstrated inhibitory effects on several tumor types. Nevertheless, its role in breast cancer and the underlying molecular mechanisms remain largely unexplored. Objectives This research aimed to investigate the anti-cancer potential of CPL in breast cancer cells. Methods The IC50 of CPL was determined using the CCK-8 assay. Subsequently, the effects of CPL on cell migration and proliferation were assessed through wound healing (scratch) and colony formation assays, respectively. Additionally, MDA and GSH levels were quantified using ELISA, while ROS production was visualized via DHE staining. Intracellular iron content was measured using an iron assay kit. Furthermore, the expression levels of p53, SLC7A11, and GPX4 were evaluated using Western blot. All experiments were performed in triplicate and independently repeated at least three times, and data were analyzed using Student’s t-test or one-way ANOVA, as appropriate. Results CPL significantly inhibited the proliferation and viability of 4T1 and MDA-MB-231 breast cancer cells in a dose-dependent manner, with IC50 values of 38.89 nM and 50.29 nM, respectively, and concomitantly suppressed cell migration and colony formation at higher concentrations. It also increased intracellular MDA and ROS and downregulated GSH, SLC7A11 and GPX4, inducing ferroptosis. siRNA knockdown of p53 attenuated CPL's effects, indicating p53's key role in CPL's anti-cancer activity. Conclusions This study provides evidence that CPL exerts anti-breast cancer effects by promoting ferroptosis through the p53/SLC7A11/GPX4 axis, highlighting its therapeutic potential as a novel agent for cancer treatment.